Triptolide and l-ascorbate palmitate co-loaded micelles for combination therapy of rheumatoid arthritis and side effect attenuation - Man Li; Guoqiang Wang; Yinyin Yan; Mengyuan Jiang; Zhirong Wang; Zhenqiang Zhang; Xiangxiang Wu; Huahui Zeng (Taylor & Francis Group, 2022)
Triptolide (TP) has its unique curative effect in the treatment of rheumatoid arthritis (RA), but its application is limited by the poor water solubility and multi-organ toxicity. We herein developed a novel nanoparticle platform composed of L-ascorbate palmitate (VP, vitamin C derivative) that can deliver TP to synergistically treat arthritis and inhibit the occurrence of oxidative stress. The TP-loaded nanoparticles (termed TP-VP NPs) showed the suitable particle size (about 145 nm) and good physical stability. TP-VP NPs effectively down-regulated IL-1β, IL-6 and TNF-α levels to inhibit the erosion of synovitis and bone tissue, and alleviate the swelling and deformation of CIA mice's feet. Compared to the TP, TP-VP NPs could inhibit effectively the oxidative stress in liver, and alleviate significantly the triptolide-induced toxicity injury in liver, kidney and testicle. The results demonstrated that TP-VP NPs is a promising triptolide delivery system for the treatment of RA, which enhances the water solubility of TP and reduces the toxicity of TP in vivo.